International legal panorama of films ownership regulation. The spanish case - Gutiérrez García, Elisa (Derecom. Derecho de la Comunicación y de Nuevas Tecnologías, 2024)
The appearance of the cinematographic work in the legal scene as an object of copyright protection was a complicated task that was both attempted to harmonize internationally and move to national legislations, along with the other existing creative realities. However, this new kind of work presented some characteristics in its creation and exploitation that made it more complex than the rest of existing works until then and that were dealt with in a different way by countries. This paper seeks to give the reader an overview of the different regulatory responses that the main legal systems have articulated in the international scene when dealing with the ownership of exploitation rights over cinematographic works, with special attention to the Spanish case.